Too much, too soon ; Loco over nata ; My Fair Lady [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
The first part describes the residents of Baguio City opposing the government's plan to develop Club John Hay into a major tourist destination; the second part is about Nata de Coco being exported to Japan; third is a stage production of My Fair Lady and an interview with its lead casts, Lea Salonga, Chinggay Alonso and director Zenaida Amador.
Too much, too soon (20 min.) -- Loco over nata (17 min.) -- My Fair Lady (10 min.).
VHS.
Reporter, Marga Ortigas.
Keywords: Alonso, Chinggoy; Amador, Zenaida; Salonga, Lea; Club John Hay; Nata de coco; Baguio City